Multi-scale approach for simulating time-delay biochemical reaction systems - Niu, Yuanling; Burrage, Kevin; Zhang, Chengjian (IET systems biology, 2015)
This study presents a multi-scale approach for simulating time-delay biochemical reaction systems when there are wide ranges of molecular numbers. The authors construct a new efficient approach based on partitioning into slow and fast subsets in conjunction with predictor–corrector methods. This multi-scale approach is shown to be much more efficient than existing methods such as the delay stochastic simulation algorithm and the modified next reaction method. Numerical testing on several important problems in systems biology confirms the accuracy and computational efficiency of this approach.